2017
DOI: 10.1016/j.cll.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacteriaceae

Abstract: Synopsis Carbapenem-resistant Enterobacteriaceae (CRE) have emerged as a major threat to modern medicine. Commonly used antibiotics are generally inactive against CRE. Therefore, timely detection of CRE in the clinical laboratory is of paramount importance. Among CRE, those producing carbapenem-hydrolyzing β-lactamase enzymes (carbapenemase-producing Enterobacteriaceae; CPE) are particularly of concern since they tend to spread among patients, and treatment of active infection is difficult. The carbapenemase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
156
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(166 citation statements)
references
References 62 publications
(57 reference statements)
3
156
0
7
Order By: Relevance
“…The biology, epidemiology, and management of CRE have been reviewed. [94][95][96][97] Recent articles have reviewed newer antibiotic therapies for CRE. 98,99 Follow-up of hospitalized CRE colonized patients demonstrated that the mean duration of colonic carriage was >1 year.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…The biology, epidemiology, and management of CRE have been reviewed. [94][95][96][97] Recent articles have reviewed newer antibiotic therapies for CRE. 98,99 Follow-up of hospitalized CRE colonized patients demonstrated that the mean duration of colonic carriage was >1 year.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…isolates that were carbapenem-non-susceptible over the last two decades, which correlated with increased use of carbapenems at our center. While the incidence of carbapenem-resistant organisms has increased worldwide over recent years (7, 46), attention has been largely focused on other carbapenem-resistant members of the Enterobacterales , such as Enterobacter spp., E. coli , and Klebsiella spp. (7).…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of carbapenem-resistant organisms has increased worldwide over recent years (7, 46), attention has been largely focused on other carbapenem-resistant members of the Enterobacterales , such as Enterobacter spp., E. coli , and Klebsiella spp. (7). As with other gram-negative species, increasing antibiotic resistance among Citrobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbapenem-hydrolyzing enzymes are categorized into Ambler classes A, B, and D (46,47). Ambler class A enzymes (serine β-lactamases; i.e., Klebsiella pneumoniae Carbapenemase [KPC] and Serratia marcescens Enzyme [SME]) can be plasmidborne or chromosomally encoded, and are active against β-lactam and carbapenem antibiotics.…”
Section: Carbapenem Resistance In Enterobacteriaceaementioning
confidence: 99%